A protein phosphatase network controls the temporal and spatial dynamics of differentiation commitment in human epidermis - Mishra, Ajay; Oulès, Bénédicte; Pisco, Angela Oliveira; Ly, Tony; Liakath-Ali, Kifayathullah; Walko, Gernot; Viswanathan, Priyalakshmi; Tihy, Matthieu; Nijjher, Jagdeesh; Dunn, Sara-Jane; Lamond, Angus I; Watt, Fiona M (eLife, 2017)
Epidermal homeostasis depends on a balance between stem cell renewal and terminal differentiation. The transition between the two cell states, termed commitment, is poorly understood. Here, we characterise commitment by integrating transcriptomic and proteomic data from disaggregated primary human keratinocytes held in suspension to induce differentiation. Cell detachment induces several protein phosphatases, five of which - DUSP6, PPTC7, PTPN1, PTPN13 and PPP3CA – promote differentiation by negatively regulating ERK MAPK and positively regulating AP1 transcription factors. Conversely, DUSP10 expression antagonises commitment. The phosphatases form a dynamic network of transient positive and negative interactions that change over time, with DUSP6 predominating at commitment. Boolean network modelling identifies a mandatory switch between two stable states (stem and differentiated) via an unstable (committed) state. Phosphatase expression is also spatially regulated in vivo and in vitro. We conclude that an auto-regulatory phosphatase network maintains epidermal homeostasis by controlling the onset and duration of commitment.
Keywords: epidermis; commitment; stem cells; differentiation; protein dephosphorylation; Boolean networks